2018
DOI: 10.17507/tpls.0811.16
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perceived Challenges of Attending a Flipped EFL Classroom in Viet Nam

Abstract: Flipped classroom is gaining more and more popularity among educators and researchers all over the world; however, its implementation in Viet Nam is still in infancy. This small-scale research project attempts to investigate students’ perceived challenges when attending a flipped English grammar class. Qualitative research design was adopted to address the research question. The participants include 34 second-year students majoring in the English language at a state university in Viet Nam. The instruments cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 18 publications
3
18
0
Order By: Relevance
“…Ansori & Nafi' (2018) examined teachers' perspectives and challenges towards the flipped classroom. Vuong, Tan, & Lee (2018) researched to see the challenges faced when students learn to use the flipped classroom model. This research was applied to first-grade students in senior high school while the previous research was applied to undergraduate students in the University.…”
Section: Efl Students' Experiences In a Flipped Reading Comprehensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ansori & Nafi' (2018) examined teachers' perspectives and challenges towards the flipped classroom. Vuong, Tan, & Lee (2018) researched to see the challenges faced when students learn to use the flipped classroom model. This research was applied to first-grade students in senior high school while the previous research was applied to undergraduate students in the University.…”
Section: Efl Students' Experiences In a Flipped Reading Comprehensionmentioning
confidence: 99%
“…As in the research of Ha et al (2019), Qader & Arslan (2019), and Love et al (2015) who implemented the flipped classroom at the University. Furthermore, previous studies, (Soliman, 2016;Ansori & Nafi', 2018;Vuong, Tan, & Lee, 2018;Ha et al, 2019;Qader & Arslan, 2019;and Love et al, 2015), applied the flipped classroom model in the usual way, namely in the classroom at school, while this research used the flipped classroom in online learning. The used of WhatsApp and Zoom is needed fo online learning.…”
Section: Efl Students' Experiences In a Flipped Reading Comprehensionmentioning
confidence: 99%
“…Turan & Akdag-Cimen (2019), who conducted a review of flipped classroom approach in English language classrooms, also reported that the use of flipped classroom approach was workable especially for the speaking and writing skills. Nevertheless, although previous studies including by Andujar et al (2020) have indicated the benefits gained by students in a flipped classroom, studies conducted by Vuong (2018) and Miragall & García-Soriano (2016) have shown that students often face challenges in participating in the flipped classroom setting.…”
Section: Introductionmentioning
confidence: 94%
“…In a flipped classroom, the learning activities that traditionally occur in the classroom, like the introduction of new material through lectures and handouts, are introduced to students outside the classroom in a digital environment; The activities that traditionally occur outside the classroom, like homework assignments and activities completed in isolation, are now completed inside the classroom. When students carry out activities and assignments in a more deeper and critical discussion with their teacher and/or their peers, they engage in active learning (Vuong et al, 2018). Usually, videos of topic are created and distributed online as pre-learning exercise.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…He placed his teaching notes (PowerPoint slides) in a digital platform and had his students go through the teaching materials before real class time. While in class time was typically used for the applications and practices new concepts that the students acquired beforehand through collaborative activities (Vuong, Tan, & Lee, 2018). Therefore, a flipped classroom is the reverse to the traditional teaching methods.…”
Section: Introductionmentioning
confidence: 99%